Increased cardiovascular mortality in people with schizophrenia: a 24-year national register study. (5th June 2017) - Westman, J.; Eriksson, S. V.; Gissler, M.; Hällgren, J.; Prieto, M. L.; Bobo, W. V.; Frye, M. A.; Erlinge, D.; Alfredsson, L.; Ösby, U.
Abstract : Aims: People who have schizophrenia die earlier from somatic diseases than do people in the general population, but information about cardiovascular deaths in people who have schizophrenia is limited. We analysed mortality in all age groups of people with schizophrenia by specific cardiovascular diseases (CVDs), focusing on five CVD diagnoses: coronary heart disease, acute myocardial infarction, cerebrovascular disease, heart failure and cardiac arrhythmias. We also compared hospital admissions for CVDs in people who had schizophrenia with hospital admissions for CVDs in the general population. Methods: This national register study of 10 631 817 people in Sweden included 46 911 people who were admitted to the hospital for schizophrenia between 1 January 1987 and 31 December 2010. Information from national registers was used to identify people who had schizophrenia and obtain data about mortality, causes of death, medical diagnoses and hospitalisations. Results: CVDs were the leading cause of death in people who had schizophrenia (5245 deaths), and CVDs caused more excess deaths than suicide. The mean age of CVD death was 10 years lower for people who had schizophrenia (70.5 years) than the general population (80.7 years). The mortality rate ratio (MRR) for CVDs in all people who had schizophrenia was 2.80 (95% confidence interval (CI) 2.73–2.88). In people aged 15–59 years who had schizophrenia, the MRR for CVDs was 6.16 (95% CI 5.79–6.54). In all people who had schizophrenia, the MRR for coronary heart disease was 2.83 (95% CI 2.73–2.94); acute myocardial infarction, 2.62 (95% CI 2.49–2.75); cerebrovascular disease, 2.4 (95% CI 2.25–2.55); heart failure, 3.25 (95% CI 2.94–3.6); and cardiac arrhythmias, 2.06 (95% CI 1.75–2.43). Hospital admissions for coronary heart disease were less frequent in people who had schizophrenia than in the general population (admission rate ratio, 0.88 (95% CI 0.83–0.94). In all age groups, survival after hospital admission for CVD was lower in people who had schizophrenia than in the general population. Conclusions: People who had schizophrenia died 10 years earlier from CVDs than did people in the general population. For all five CVD diagnoses, mortality risk was higher for those with schizophrenia than those in the general population. Survival after hospitalisation for CVDs in people who had schizophrenia was comparable with that of people in the general population who were several decades older.